Determinants of Export Survival in the Lao PDR - Stirbat, Liviu (World Bank, Washington, DC, 2013)
This paper explores a rich dataset of monthly firm-level data on the population of exporters of Lao PDR from 2005 to 2010. The survival analysis uses a discrete-time logistic model based on firm-product-destination triplets while accounting for unobserved heterogeneity. It looks in detail at the role played by two important and related determinants of survival: experience and networks. These are particularly relevant for developing countries, where relevant export experience in firms is likely to be limited and networks leveraging it all the more important. The analysis reveals the positive impact of having prior experience with the export product and destination, experience with importing, as well as using a developed neighboring country as launch platform. Networks are found to be most relevant when they are most specific -- the largest impact comes from province level aggregations of firms selling the same product in the same market during a particular month. A competing risks model was also investigated to discern the impact of these determinants on the likelihood of experiencing an upgrade to a superior product versus termination when a trade contract ends.